Analisis Filogenetik Cryptic species Apis cerana Fabricius, 1793 Berdasarkan Gen 16S rRNA - Puspitasari, Amira; Budiarsa, I Made; Ashari, Abdul; Dhafir, Fatmah; Windarsih, Yulia; Trianto, Manap (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Apis cerana is a member of the Insecta class grouped in the order Hymenoptera. Phylogenetic analysis is used to describe the kinship of living things through phylogeny trees. This study aims to describe the phylogenetic relationship of cryptic species in Apis cerana based on the 16S rRNA gene. Sampling use the cruising method in various regions, the DNA isolation, DNA amplification, sequencing, followed by bioinformatics analysis using GeneStudio, DNASTAR, MESQUITE, and MEGA 11. The result showed that phylogenetic analysis with the Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods produced a phylogenetic tree that illustrates clear evolutionary relationship. A. cerana from Central Sulawesi is more closely related to other A. cerana species in the same clade, while other species are separated. The result of this study show a clear pattern of kinship between A. cerana populations.